Analysis of the Effect of FDR, BOPO, Inflation & GDP on Non-Performing Financing (NPF) in Islamic Windows Bank for the 2018-2023 Period - Ramadini, Nazwa Putri; Ruhana, Nafisah (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Non-Performing Financing (NPF) is a common risk in Islamic banking, arising from the decline in financing quality from current to substandard, doubtful, or loss categories. Islamic Windows Bank (UUS) have experienced a greater increase in NPF compared to the growth in financing distribution. This study aims to examine the effect of the Financing to Deposit Ratio (FDR), Operating Expenses to Operating Income (BOPO), inflation, and Gross Domestic Product (GDP) on Non-Performing Financing (NPF) in Islamic Windows Bank in Indonesia during the 2018–2023 period. This research uses secondary data obtained from the financial reports of UUS published on the official website of the Financial Services Authority (OJK) and data from Statistics Indonesia (BPS). A total of 18 samples were selected using purposive sampling technique. The method employed in this study is panel data regression. Data were processed using STATA version 17. The results show that, partially, BOPO and GDP have a significant effect on NPF, while FDR and inflation do not have a partial effect on NPF.